Spatial and temporal changes in SO2 regimes over China in the recent decade and the driving mechanism - T. Wang (Atmospheric Chemistry and Physics, 2018)
The spatial and temporal changes in SO2 regimes over China during 2005 to 2016 and their associated driving mechanism are investigated based on a state-of-the-art retrieval dataset. Climatological SO2 exhibits pronounced seasonal and regional variations, with higher loadings in wintertime and two prominent maxima centered in the North China Plain and the Cheng-Yu District. In the last decade, overall SO2 decreasing trends have been reported nationwide, with spatially varying downward rates according to a general rule – the higher the SO2 loading, the more significant the decrease. However, such decline is in fact not monotonic, but instead four distinct temporal regimes can be identified by empirical orthogonal function analysis. After an initial rise at the beginning, SO2 in China undergoes two sharp drops in the periods 2007–2008 and 2014–2016, amid which 5-year moderate rebounding is sustained. Despite spatially coherent behaviors, different mechanisms are tied to North China and South China. In North China, the same four regimes are detected in the time series of emission that is expected to drive the regime of atmospheric SO2, with a percentage of explained variance amounting to 81 %. Out of total emission, those from the industrial sector dominate SO2 variation throughout the whole period, while the role of household emission remains uncertain. In contrast to North China, SO2 emissions in South China exhibit a continuous descending tendency, due to the coordinated cuts of industrial and household emissions. As a result, the role of emissions only makes up about 45 % of the SO2 variation, primarily owing to the decoupled pathways of emission and atmospheric content during 2009 to 2013 when the emissions continue to decline but atmospheric content witnesses a rebound. Unfavorable meteorological conditions, including deficient precipitation, weaker wind speed and increased static stability, outweigh the effect of decreasing emissions and thus give rise to the rebound of SO2 during 2009 to 2013.